Evaluation of the effectiveness of the standard traditional Korean medicine-based health promotion program for disadvantaged children in South Korea - Eunhye Hyun; Jiseon Ryu; Kibong Kim; Sangjae Lee; Seungtae Kim; Byungmook Lim (BMC, 2022)
Abstract Background Traditional Korean Medicine (TKM) is highly integrated with the modern health care system of South Korea and is actively used in the public health field. Since 2014, the Ministry of Health and Welfare of South Korea has supported the development of standard models for TKM-based health promotion programs. This study aimed to develop and evaluate a standard TKM-based health promotion program for disadvantaged children. Methods Using convenience sampling, we recruited 16 Community Children's Centers (CCCs) located in Busan and Yangsan, South Korea, which are welfare daytime facilities for children from socially disadvantaged families. The CCCs were divided into two groups of eight CCCs-intervention CCCs and control CCCs-through random allocation, and children in each group were selected as subjects for the study. For 12 weeks, the TKM-based health promotion program developed in this study along with the basic services of CCCs were applied to children in the intervention group, and only the basic services of CCCs were provided to children in the control group. Data were obtained through pre- and post-surveys with the legal representatives of the children prior to implementing the program and after the 12-week program, respectively. The outcome variables-the number of outpatient visits, absences, lateness/early leaves, infectious symptoms, and EuroQol-5D and EQ-visual analog scale scores-were measured and statistically compared between the groups by descriptive analysis, chi-square test, t-test, and difference-in-differences model with regression analysis. Results At baseline, there were 156 children in the intervention group and 153 children in the control group, among which 155 and 147 children, respectively, were included in the analysis. Results indicated that the number of outpatient visits was significantly lower (by 65%) in the intervention group than in the control group (p = 0.03), and this was similar in the sensitivity analysis. Regarding other outcome variables, the effects were not consistently significant. Conclusions A standard TKM-based health promotion program has the potential to improve the health of disadvantaged children. In the future, studies with long-term interventions and a larger sample are needed to enhance the applicability of these programs in communities.